Absence and finitude: The apocalyptic representation in Tatsuki Fujimoto's Fire Punch. - Casoni Henriquez, Franco (Resonancias. Revista de Filosofía, 2023)
This research proposes a review of the idea of ​​the apocalyptic present in Tatsuki Fujimoto's Fire Punch from the representation that is made in it of the eschatological and the scope that the idea of ​​the apocalyptic has within the story. Thus, the actions and motivations of the characters in this work will be analyzed according to the meaning of the destruction portrayed in the work. For this there are two central moments of the investigation: first, the problematization of the apocalyptic and the scope that this phenomenon has in this manga (Deleuze, Kant and Parkinson Zamora) and second, the appearance of presence and absence in Fire Punch (Heidegger, Derrida, Fisher) and its illuminating or revealing function.